Force production, balance control and muscle activation in different sitting positions - pilot study for disabled sit sledge cross-country skiers - Rapp, W.; Lindinger, S. J.; Lappi, T.; Ohtonen, O.; Linnamo, V. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
The aim was to create optimized sledges for impaired cross-country and biathlon athletes based on biomechanical relationships for the Winter Paralympics 2014 in Sochi. The challenge in relation to this is that the degree and nature of the impairment is different for each athlete and that athletes can only optimally utilize their strength for forward propulsion in a very specific seated position. For this reason, each athlete essentially requires an individual solution in construction of sit sledges.